2014
DOI: 10.1155/2014/816246
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Reoperation for Bleeding following Liver Transplantation

Abstract: Introduction. This study's objective was to identify risk factors associated with reoperation for bleeding following liver transplantation (LTx). Methods. A retrospective study was performed at a single institution between 2001 and 2012. Operative reports were used to identify patients who underwent reoperation for bleeding within 2 weeks following LTx (operations for nonbleeding etiologies were excluded). Results. Reoperation for bleeding was observed in 101/928 (10.8%) of LTx patients. The following characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
(43 reference statements)
2
21
1
Order By: Relevance
“…In our series, the most common indication of early reoperation was postoperative hemorrhage followed by vascular flow complications. The rate of early reoperation due to bleeding (9.6%) is comparable with previous reported series in which the rate varied from 8% to 27% . Hemostatic balance is a concern for patients with liver failure and LT recipients .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our series, the most common indication of early reoperation was postoperative hemorrhage followed by vascular flow complications. The rate of early reoperation due to bleeding (9.6%) is comparable with previous reported series in which the rate varied from 8% to 27% . Hemostatic balance is a concern for patients with liver failure and LT recipients .…”
Section: Discussionsupporting
confidence: 85%
“…Untreated, those complications can lead to graft failure and death . Reoperation is frequently required post‐LT (9.2% to 34%) to treat these severe complications …”
Section: Introductionmentioning
confidence: 99%
“…Benson et al [16] reported a significant dose dependent association between transfusion of RBC, fresh frozen plasma (FFP) and platelets and post-operative infections. Number of RBC units transfused was predictive for re-operation post LT in one centre [17] , an event associated with high financial burden and excess mortality [18] . Mechanisms for poor outcomes and increased postoperative infection associated with RBC transfusion are not fully understood.…”
Section: Drivers For Transfusion-free Transplantationmentioning
confidence: 97%
“…The vasoactive effects of platelets may cause other negative systemic consequences such as pulmonary hypertension and haemodynamic disturbance. In one study platelet infusion was associated with reduced re-operation rates, a reminder that balancing risks of bleeding and side effects is a real clinical challenge [18,23] .…”
Section: Drivers For Transfusion-free Transplantationmentioning
confidence: 99%
“…However, blood products are also critical for resuscitation and hemostasis in the coagulopathic bleeding patient. A conservative platelet transfusion strategy has been associated with increased risk for re‐operation due to bleeding . Platelets are also a key source of serotonin, which is important for liver regeneration …”
Section: Introductionmentioning
confidence: 99%